Lewis acids promote the catalytic selectivity to polyoxymethylene dimethyl ethers PODE3, 4. (1st June 2019) - Qi, Jianguang; Hu, Yufeng; Jiang, Siqi; Ma, Weiting; Yang, Zhenyu; Wang, Yichuan
Abstract: Polyoxymethylene dimethyl ethers (PODE n with n = 3–8) is a new biofuel that has a great potential to become one of the competitive alternative fuels for diesel engine. It also plays a crucial role in expansion of C1 chemical industry. Because PODE6–8 tends to precipitate in PODE3–8 /diesel blends at low temperatures, it is very important to increase the selectivity to PODE3, 4 and to decrease the selectivity to PODE6–8 . Here a series of Lewis acids were used for the first time as catalyst to synthesize PODE n from methylal and trioxane. For the investigated Lewis acids, MgCl2 yielded the greatest selectivity to PODE3, 4 and the smallest selectivity to PODE5–8 . Similar selectivity to PODE3, 4 and much lower selectivity to PODE5–8 can be achieved by using optimized reaction time and using MgCl2 in place of the traditional catalyst H2 SO4 and ionic liquids catalysts [NOP][TFO] (1-octyl-2-pyrrolidinonium trifluoromethanesulfonate) and [NOP][DNBSA] (1-octyl-2-pyrrolidinonium 2, 4-dinitrobenzenesulfonate) as catalyst. In addition, these Lewis acids have many advantages over the traditional catalysts and ionic liquids catalysts, including low corrosiveness, high separability, and low cost.